PENERAPAN STRATEGI PEMBELAJARAN MODELLING THE WAY UNTUK MENINGKATKAN HASIL BELAJAR PENDIDIKAN AGAMA ISLAM (PAI) SISWA KELAS IV SD NEGERI 010 BANJAR PANJANG KECAMATAN KERUMUTAN - Euis Anegawati (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
The background of this study was the low learning outcomes in Islamic Education (PAI) among fourth-grade students of SD Negeri 010 Banjar Panjang, Kerumutan Subdistrict. Of the 28 students, only 12 achieved the school’s minimum mastery criterion (KKM) of 65. The low PAI learning outcomes were caused by several factors: (a) the instructional methods used by teachers were predominantly lectures, discussions, and assignments; (b) teachers did not provide concrete examples closely related to students’ daily lives when presenting the material; (c) teachers tended to assign students to work only on textbook exercises; and (d) teachers rarely communicated learning objectives and provided limited motivation to students. This study employed classroom action research conducted in two cycles by implementing the Modeling the Way learning strategy. Based on the research results, the data showed that PAI learning outcomes improved in each cycle. This improvement was evidenced by: (a) increased teacher activity in each cycle, with the first cycle meeting I obtaining a score of 3 (60.00%), the first cycle meeting II also obtaining a score of 3 (60.00%), the second cycle meeting I obtaining a score of 4 (80.00%), and the second cycle meeting II obtaining a score of 5 (100%); and (b) improved student PAI learning outcomes, with the average score in the first cycle reaching 71 and increasing to 77.3 in the second cycle. In addition, students’ mastery learning also increased, with 20 students (71.00%) achieving mastery in the first cycle and 24 students (85.00%) in the second cycle. Based on these findings, it can be concluded that the implementation of the Modeling the Way learning strategy effectively improves PAI learning outcomes of fourth-grade students at SD Negeri 010 Banjar Panjang.